Prevalencia y factores desencadenantes de la cetoacidosis diabética en pacientes que ingresan al área de urgencias del Hospital General Regional No. 1 Charo - Escutia Castro, Juan Carlos (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
Introduction: DKA is a decompensation of diabetes with relatively low prevalence, with multiple triggering factors and variable mortality without figures adjusted to our population. Objectives: Determine the prevalence of DKA and know the main risk factors in the population of HGR 1. Material and methods: Quantitative, retrospective and cross-sectional study of admissions to the emergency department of HGR 1, from January to December 2023, 59 were included. patients with a diagnosis of DM 1 and 2, with ADA criteria for DKA, over 18 years of age, both sexes. Sociodemographic and clinical variables were collected; Descriptive and inferential statistical tests were used to determine association between variables with a significant value p<0.05 and SPSS v.23 program for analysis. Results: With a general prevalence of 0.348% and 9.06% among diabetics, 61% had severe DKA, the most prevalent type of DM was type 2 (74.58%), with no relevance to sex (47.8% vs 52.5%) (p = 0.87), poor adherence to treatment stood out as a risk factor present in 59.3% and infections only 50.84%, mortality of 5.1%. Conclusions: The prevalence and mortality of CAD is in the international average among developed countries; however, unlike these analyses, DM2 stood out as the underlying pathology and poor adherence to treatment as the main risk factor.

Introducción: La CAD es una descompensación de la diabetes con relativa baja prevalencia, con múltiples factores desencadenantes y mortalidad variable sin cifras ajustadas a nuestra población. Objetivos: Determinar la prevalencia de la CAD y conocer los principales factores de riesgo en la población del HGR 1. Material y métodos: Estudio cuantitativo, retrospectivo y transversal de ingresos a urgencias del HGR 1, de enero a diciembre 2023, se incluyeron a 59 pacientes con diagnóstico de DM 1 y 2, con criterios de CAD por la ADA, mayores de 18 años, ambos sexos. Fueron recabadas variables sociodemográficas y clínicas; Se emplearon pruebas de estadística descriptiva e inferencial para determinar asociación entre variables con valor significativo p<0.05 y programa SPSS v.23 para análisis. Resultados: Con prevalencia general de 0.348% y 9.06% entre diabéticos, el 61% fue CAD severa, el tipo de DM más prevalente fue el tipo 2 (74.58%), sin relevancia en sexo (47.8% vs 52.5%) (p=0.87), el mal apego al tratamiento destacó como factor de riesgo presente en el 59.3% y las infecciones solo 50.84%, mortalidad de 5.1%. Conclusiones: La prevalencia y mortalidad de CAD se encuentra en el promedio internacional entre países desarrollados, sin embargo, a diferencia de dichos análisis, destacó la DM2 como patología de base y el mal apego al tratamiento como principal factor de riesgo.
Facultad de Ciencias Médicas y Biológicas. Instituto Mexicano del Seguro Social. Especialidad en Urgencias Médicas
Keywords: info:eu-repo/classification/cti/3; FCMB-E-2025-0256; Diabetes mellitus; Factor de riesgo; Insulina; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19133